Simulation of Hp(10) and effective dose received by the medical staff in interventional radiology procedures. (7th August 2019) - Ferrari, P; Becker, F; Jovanovic, Z; Khan, S; Bakhanova, E; Principi, S; Krstic, D; Pierotti, L; Mariotti, F; Faj, D; Turk, T; Nikezic, D; et al.
Abstract: Interventional radiology and cardiology are widespread employed techniques for diagnosis and treatment of several pathologies because they avoid the majority of the side-effects associated with surgical treatments, but are known to increase the radiation exposure to patient and operators. In recent years many studies treated the exposure of the operators performing cardiological procedures. The aim of this work is to study the exposure condition of the medical staff in some selected interventional radiology procedures. The Monte Carlo simulations have been employed with anthropomorphic mathematical phantoms reproducing the irradiation scenario of the medical staff with two operators and the patient. A personal dosemeter, put on apron, was modelled for comparison with measurements performed in hospitals, done with electronic dosemeters, in a reduced number of interventional radiology practices. Within the limits associated to the use of numerical anthropomorphic models to mimic a complex interventional procedure, the personal dose equivalent, H p (10), was evaluated and normalised to the simulated Kerma-Area Product, KAP, value, indeed the effective dose has been calculated. The H p (10)/KAPvalue of the first operator is about 10 μ Sv/Gy.cm 2, when ceiling shielding is not used. This value is calculated on the trunk and it varies of +/−30% moving the dosemeter to the waist or to the neck. The effective dose, normalised to the KAP value, varies between 0.03 and 0.4 μ Sv/Gy.cm 2 . Considering all the unavoidable approximation of this kind of investigations, the comparisons with hospital measurement and literature data showed a good agreement allowing to use of the present results for dosimetric characterisation of interventional radiology procedures.